Assessing Phytoplankton Activities in the Seasonal Ice Zone of the Greenland Sea Over an Annual Cycle. Issue 11 (8th November 2018) - Mayot, N.; Matrai, P.; Ellingsen, I. H.; Steele, M.; Johnson, K.; Riser, S. C.; Swift, D.
Abstract: In seasonal ice zones (SIZs), such as the one of the Greenland Sea, the sea ice growth in winter and subsequent melting in summer influence the phytoplankton activity. However, studies assessing phytoplankton activities over complete annual cycles and at a fine temporal resolution are lacking in this environment. Biogeochemical‐Argo floats, which are able to sample under the ice, were used to collect physical and biogeochemical data along vertical profiles and at 5‐day resolution during two complete annual cycles in the Greenland Sea SIZ. Three phytoplankton activity phases were distinct within an annual cycle: one under ice, a second at the ice edge, and a third one around an open‐water subsurface chlorophyll maximum. As expected, the light and nitrate availabilities controlled the phytoplankton activity and the establishment of these phases. On average, most of the annual net community production occurred equally under ice and at the ice edge. The open‐water subsurface chlorophyll maximum phase contribution, on the other hand, was much smaller. Phytoplankton biomass accumulation and production thus occur over a longer period than might be assumed if under ice blooms were neglected. This also means that satellite‐based estimates of phytoplankton biomass and production in this SIZ are likely underestimated. Simulations with the Arctic‐based physical‐biologically coupled SINMOD model suggest that most of the annual net community production in this SIZ results from local processes rather than due to advection of nitrate from the East Greenland and Jan Mayen Currents. Key Points: In the seasonal ice zone, significant phytoplankton activity occurs under ice earlier in the season At the ice edge, a high phytoplankton biomass is present around a subsurface chlorophyll maximum feature that persists into summer Half of the annual Net Community Production occurs under ice and the other half at the ice edge